Medial Ulnar Collateral Ligament Reconstruction: A Dual Docking, 4-Ply Reconstructive Technique - Patrick M. Connor MD, FAOA; Alexander Bitzer MD (SAGE Publishing, 2022)
Background: Ulnar collateral ligament injuries are common in the overhead-throwing athlete as the anterior band of this ligament is the primary soft tissue static stabilizer to valgus stress during a throwing motion. Various surgical techniques have been described over the past 30 years to address these injuries including Jobe, modified Jobe, docking, 3-stranded docking, Graftlink, and anatomic repairs with good to excellent results. Nevertheless, modifications to these techniques may increase the strength and survival of the reconstruction, which may expedite and optimize postoperative rehabilitation and return to play. Indications: This is a reproducible technique that provides excellent outcomes. We believe a 4-ply construct, with the addition of a high tensile strength suture tape, may provide superior biomechanical properties compared to other reconstructive techniques. Biomechanical testing for this technique is currently underway. Technique Description: Medial ulnar collateral ligament reconstruction using a gracilis autograft passed from proximal to distal, secured at the ulna with a cortical button tension loop construct, and then repassed from distal to proximal with the addition of a high strength suture in parallel to function as an internal brace. Together, this creates a reinforced, 4-ply, ulnar collateral ligament reconstruction with excellent tensile strength. Other advantages of this technique are that it avoids bony bridge fracture between ulnar tunnels, it preserves ulnar bone stock, creates a more anatomic insertion at the sublime tubercle and provides a simple method to tension the entire graft construct. Results: The expected outcomes from this procedure are consistently positive with recent literature reporting greater than 90% of patients having an excellent outcome and over 80% of overhead athletes returning to sport at or above previous level. Conclusion: This specific technique provides a rigid, high-tensile strength reconstruction with excellent outcomes and a high percentage of return to play. Additionally, this technique avoids various technical pitfalls by utilizing cortical button suspensory fixation at the ulna which minimizes complications such as ulnar tunnel conversion and iatrogenic injury to the ulnar nerve when drilling posterior to the sublime tubercle as is necessary with other techniques.